O romance dialético em José Saramago - Bonaldo, Deivis Jhones Garlet (2016)
Studies about the work of José Saramago, especially in the novel genre, are generally of a focus on political and ideological content represented in the narratives. Topics such as the question of democracy, the hypocrisy of the dominant social sectors, individualism egocentric and a pragmatic utilitarianism, violence, besides the increase of rationality dominated by the logic of capital, finally, dehumanization and the lack of a substantive policy - criticism of the author as a citizen - are transformed into literary material, as reflections and refractions of the ideological environment in which the writer was inserted, especially in relation to the late twentieth century and early twenty-first. Certainly such contents allow different ways of understanding, based on different theories and methods, justifying, of course, multiple hermeneutic results, which contributes to the evidence of the polysemic richness of the works of the Portuguese author. From the analysis of the novels Essay on the blindness, Essay on the lucidity and The flashes of death along the comparison with literary criticism, we propose the thesis that the axiological content refracted in Saramago prose takes place because of a structure, here bounded to the plot and the form and function of the narrator, the character and irony, eminently dialectical - which assumes the condition principle of aesthetic construction. In terms of plots, the progression of actions takes place dialectically, converging to an open textual and narrative explicit in becoming, directing - the strength of the dynamics of the fictional world - the player to return to the incipit and epigraphs, so that being aware of the harmony of appearance and essence of contradictions struggle. Surely, the narrative instance, the character and the irony, part of a structured whole, contribute decisively to the realization of continuous and discontinuous movement of the novelistic universe, as well formatted and functional by the general aesthetic criterion. As a whole structured, the Saramago work has an aesthetic principle dialectical and political postulate and humanistic-democratic ideological, fully converged to produce the axiological sense because of man, rationality, freedom and responsibility, that is, a ethical individual according to his phenomenal eventicidade. Finally, the work of José Saramago erects itself as a carrier-sign object of axiological charge rapidly symbolic counterpoint to the world of globalization and the objectification of abstract novelistic structure of narratives, we entertained the need to consider the aesthetic principle dialectical as essential, either to corroborate or resize aspects of content, is to understand the artistic position and citizen of the portuguese writer.